Inserção de física moderna e contemporânea no ensino médio: a ligação entre teorias clássicas e modernas sob a perspectivas da aprendizagem significativa - Lino, Alex (2010)
This paper aimed verify if the teaching of Modern and Contemporary Physics at high school may be potentially significant when inserted in a combined way with the teaching of Classical physics. The approached topics have in common the concepts of heat and energy. During the classes about the process of heat transference, it was approached the issue about the blackbody radiation problem, inserting concepts of Quantum Physics, as the quantization of energy and the concept of quanta. It always started from a problematization of a classical concept to its explanation according to the Modern and Contemporary physics. In order to reach this objective the classes were prepared based on the theory of significant learning of David Ausubel, starting from more general concepts followed by deeply specification. It was also based on the theory of Epistemological Obstacles of Gaston Bachelard. The research was developed with second year students of a private High School in the State of São Paulo, at Paraguaçu Paulista city. The data was analyzed through questionnaires according to the theory of significant learning and with the assistance of conceptual maps according to Novak and Gowin. The data analysis reveled that many of the students suffered obliteration of their subsumers and the maps shows us highly organized hierarchies of the cognitives structures of the students, this is indication of significant learning. It was also observed, mainly through the analysis of the conceptual maps, relation between classical physics and Concepts of Modern physics inserted in organized structures. This process allowed us to conclude that exists a perspective of significant learning when it is done a relation between classical and modern theories inserted in this context.